Survival Rate of Tunneled Hemodialysis Catheters in Patients on Hemodialysis due to Chronic Kidney Disease (CKD) - Faiza Sattar, Maryam Siddiqa, Asim Zahoor, Umer Zahoor, Ayesha Manzoor, Ali Zahoor (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the survival rate and reasons of failure of tunneled hemodialysis catheters in patients on hemodialysis due to chronic kidney disease (CKD). Study Design: Prospective case series. Place and Duration of Study: Department of Nephrology, Sheikh Zayed hospital Rahim Yar Khan from 1-June-2020 to 30-June-2021. Methodology: A total number of 195 patients of CKD in whom tunneled hemodialysis catheters (HDCs) were inserted for hemodialysis were included. Data regarding baseline study variables e.g. age, and gender, site of insertion and reason for removal was also collected. All patients were followed for 06 months to determine the survival rate of tunneled hemodialysis catheters. Results: Mean age in this study was 46.79±13.54 years. There was 130 (66.7%) male population. HDC was inserted in Jugular vein in 184 (94.4%) patients and in subclavian vein in only 11 (5.6%) patients. HDCs were survived in 156 (80%) patients at 3 months and in 134 (68.7%) patients at 6 months follow-up. The reasons for removal of HDCs were sepsis in 16 (8.2%) patients, catheter clotting in 14 (7.7%) patients and mechanical damage in 8 (4.1%) patients. On univariate analysis, we did not find any statistical association of advanced age, female gender, diabetes and hypertension with failure of HDCs. Conclusion: The 06 month’s survival rate of HDCs was 68.7%. Sepsis was the predominant cause of failure of these catheters.